FLUKTUASI CURRENT ACCOUNT DAN PORTFOLIO INVESTMENT TERHADAP CADANGAN DEVISA INDONESIA - Dewi Mahrani Rangkuty; Rusiadi Rusiadi (Universitas Teuku Umar, 2020)
Foreign exchange reserves are the central bank's assets as a source of financing funds for international trade transactions in the global market. This research aims to analyze the current account fluctuations and portfolio investment against Indonesia's foreign exchange reserves. By using the time series 1981-2018 data sourced from the World Bank, the research results based on the method Vector Error Correction Model (VECM) indicates that the current account and the foreign exchange reserves have a two-way causality relationship and portfolio investment has a two-way causality relationship at Lag 3. The short-term estimate shows that the current account has a significant positive effect while the portfolio of investments affects negatively and significantly against the foreign exchange reserves. Long-term estimation of current account and portfolio investment is a positive and significant effect on foreign exchange reserves. Variance decomposition on short-term, intermediate and long-length contributions to the first largest foreign exchange reserves described by the foreign exchange reserves variable itself. The government should maintain the position of balance of transactions running on a surplus condition to support the increase in the number of foreign exchange reserves from time to time to encourage the acceleration of increasing the number of foreign exchange reserves cause in the short, medium and long-term first contribution to the variable foreign exchange reserves are on the foreign exchange reserves.Keywords: current account, exchange rate, GDP per capita, portfolio investment, reserves